Workplace Spirituality and Mental Well-being: Mediating Roles of Self-Compassion and Mindfulness in the Public Sector - Abiyasa; Sandi Nasrudin Wibowo (Interdisciplinary Social Studies, 2026)
This research examines the importance of mental well-being among public-sector employees who operate under bureaucratic pressure, demanding service responsibilities, and high administrative accountability. The objective of this research is to analyze the influence of workplace spirituality on mental well-being, with self-compassion and mindfulness as mediating variables among sub-district government employees in Cirebon Regency. A quantitative explanatory design was employed, involving 205 respondents selected through simple random sampling. Data were analyzed using Partial Least Squares–Structural Equation Modeling (PLS-SEM). The results indicate that workplace spirituality has a positive and significant effect on self-compassion and mindfulness. Furthermore, both self-compassion and mindfulness significantly enhance mental well-being, with mindfulness demonstrating the strongest direct influence. Mediation analysis confirms a significant sequential pathway in which workplace spirituality improves mental well-being through the development of self-compassion and mindfulness. These findings suggest that a meaningful and value-aligned work environment strengthens internal psychological resources that support sustainable employee resilience. Practically, this study provides evidence-based recommendations for public institutions to cultivate value-driven organizational cultures and implement mindfulness-based initiatives to enhance employee mental well-being